Springer handbook of inorganic photochemistry - Bahnemann, D.; Patrocinio, Antonio Otavio T. (Springer, 2022)
The handbook comprehensively covers the field of inorganic photochemistry from the fundamentals to the main applications. The first section of the book describes the historical development of inorganic photochemistry, along with the fundamentals related to this multidisciplinary scientific field. The main experimental techniques employed in state-of-art studies are described in detail in the second section followed by a third section including theoretical investigations in the field. In the next three sections, the photophysical and photochemical properties of coordination compounds, supramolecular systems and inorganic semiconductors are summarized by experts on these materials. Finally, the application of photoactive inorganic compounds in key sectors of our society is highlighted. The sections cover applications in bioimaging and sensing, drug delivery and cancer therapy, solar energy conversion to electricity and fuels, organic synthesis, environmental remediation and optoelectronics among others. The chapters provide a concise overview of the main achievements in the recent years and highlight the challenges for future research. This handbook offers a unique compilation for practitioners of inorganic photochemistry in both industry and academia.